Attitudes of the majority population towards the civic and political participation of immigrants in Slovenia - Medvešek, Mojca (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
The civic and political participation of immigrants in the receiving country are important dimensions of the integration process. However, immigrants often encounter various barriers in accessing individual forms of participation, either due to legal barriers or due to informal opposition from the majority population. This article aims to examine the attitudes of the majority population towards the civic and political participation of immigrants in Slovenia and the factors influencing such attitudes. The survey on a representative sample of Slovene residents revealed predominantly negative attitudes of the majority population towards both civic and political participation of immigrants. Particularly notable is the opposition to granting immigrants active and passive voting rights. Relevant factors influencing such attitudes include gender, age, education, the type of settlement in which the respondents reside, and their ideological orientation.
Keywords: attitude of the majority population; civic participation; civilnodružbena participacija; immigrants; odnos večinskega prebivalstva; political participation; politična participacija; priseljenci; Slovenia; Slovenija